Outcome of Pregnancies in Female Patients With Inflammatory Bowel Diseases Treated With Vedolizumab. (3rd October 2018) - Moens, Annick; van Hoeve, Karen; Humblet, Evelien; Rahier, Jean-François; Bossuyt, Peter; Dewit, Sophie; Franchimont, Denis; Macken, Elisabeth; Nijs, Jochen; Posen, Annelies; Strubbe, Beatrijs; Van Hootegem, Anneleen; et al.
Abstract: Background and Aims: Vedolizumab is an IgG1 anti-α4β7 integrin antibody approved for the treatment of inflammatory bowel diseases [IBD], but without clear safety data during conception, pregnancy and nursing. Animal studies showed that mucosal vascular addressin cell adhesion molecule 1 [MAdCAM-1] is expressed by maternal vessels in the placenta and recruits α4β7-expressing cells that are considered important for maternal/fetal tolerance. Blocking this interaction by vedolizumab might affect this process. We aimed to evaluate pregnancy outcomes in vedolizumab-treated female IBD patients. Methods: We conducted a retrospective, multicentre Belgian observational study. Details on disease activity, prenatal complications, delivery and neonatal outcome were collected through a case report form. Results: Twenty-four pregnancies were reported. Five women had active disease at conception and one patient flared during pregnancy. There were 23 live births. Complications were observed in 25% of pregnancies [premature rupture of membranes, pre-eclampsia, miscarriage, elective termination and stillbirth] and in 35% of infants [prematurity, intra-uterine growth retardation, small for gestational age and congenital malformations including hip dysplasia, pulmonary valve stenosis and Hirschprung's disease]. Vedolizumab was continued throughout pregnancy in two females and stopped in the 1st and 2nd trimester in five and 16 patients, respectively. For live born children, the median [interquartile range] gestational age, weight and Apgar score 5 min after birth were 39 [37–39.6] weeks, 3270 [3080–3585] grams and 10 [9–10], respectively. Conclusions: Although several complications were observed, both in mothers and in newborns, no firm conclusions can be drawn. Awaiting prospective and controlled registries, vigilance and strict follow-up of pregnant patients treated with vedolizumab seems mandatory.